Exploring the relationship between saturated hydraulic conductivity and roots distribution: two case studies in Garfagnana (Northern Tuscany, Italy) and Zollikofen (Bern, Switzerland) - Marzini, Lorenzo; Papasidero, Michele Pio; D’Addario, Enrico; Schwarz, Massimiliano; Disperati, Leonardo (Frontiers in Sustainability, 2025)
Soil hydraulic conductivity and root distribution represent two important parameters toward the engineering applications, ranging from quantification of hydrological and geotechnical processes (e.g., water runoff, shallow landslides) to agricultural management and forestry practices. To investigate the relationship among these soil parameters, two study areas located in Italy (Garfagnana, Tuscany) and Switzerland (Zollikofen, Bern) were selected. Root Area Ratio (RAR) and soil saturated hydraulic conductivity (Ks) data were collected through the application of the trench method and the constant hydraulic head (Aardwark permeameter) and falling-head methods, respectively. Results highlight that Root Area Ratio concentrates in the first soil layers and decreases sharply following deeper layers. Root Area Ratio and soil saturated hydraulic conductivity show positive linear correlation that depends on the forest station. Our results support the hypothesis that the presence of roots represent a key factor in preferential infiltration and, therefore, hydrological models applied for the runoff modelling, slope stability and soil erosion can be improved considering the spatial distribution of roots derived by field measurement and/or remote sensing data.